Can people living with and beyond colorectal cancer make lifestyle changes with the support of health technology: A feasibility study. Issue 2 (9th April 2022) - Nelson, Victoria; Cross, Amanda J.; Powell, Jonathan; Shaw, Clare
Abstract: Background: Rates of cancer survival are increasing, with more people living with and beyond cancer. Lifestyle recommendations for cancer survivors are based largely on extrapolation from cancer prevention recommendations. This feasibility study was designed to investigate diet and physical activity variables linked to primary prevention and digital behaviour change interventions in cancer survivors and delivered by an oncology dietitian to plan for future research. Methods: In this 2‐month feasibility study, participants who had completed treatment for colorectal cancer were invited to complete online food diaries, underwent physical activity assessment, attended fortnightly telephone consultations with an oncology dietitian and completed an evaluation form. The baseline food diaries were used to help participants pick two lifestyle changes to focus on throughout the intervention. Demographic and clinical data were analysed using descriptive statistics. Results: In total, 996 patients were screened for eligibility; of these, 78 were eligible to approach and 69 were approached, resulting in 20 participants consenting to take part. Overall, the intervention was acceptable with 65% of participants completing an online food diary and 70% engaging with the dietitian over the telephone. The intervention received good feedback, with 100% of those completing the evaluation form reporting they felt supported and found it helpful. Conclusions: The present study offers preliminary evidence that a lifestyle intervention delivered by an oncology dietitian using digital behaviour change interventions (DBCIs) to cancer survivors is feasible and accepted by participants and providers. Abstract : Participants in the study identified that they preferred a combination of face to face and telephone follow up offered on a monthly basis starting 3 weeks after treatment to support lifestyle changes. Key points: The offer to participate in a study on diet and physical activity should be embedded in the colorectal cancer (CRC) pathway. All patients should be offered the opportunity to participate following completion of their CRC treatment. It is feasible to use a specialist dietitian led programme with digital behaviour change interventions using multiple methods including face‐to‐face, telephone or video to provide individualised advice. Participants prefer a longer intervention with monthly follow‐up.